2006
DOI: 10.1029/2005jd006658
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants and submicron sea spray generation

Abstract: [1] Laboratory experiments have been carried out to elucidate the role of surfactants on the primary marine aerosol production of submicron marine aerosols. A synthetic surfactant SDS was used in conjunction with artificially generated seawater, and the resultant bubble-mediated aerosol produced was observed. At 23°C, the aerosol distribution resulting from the use of surfactant-free seawater comprised three modes: (1) a dominant accumulation mode at 110 nm; (2) an Aitken mode at 45 nm; and (3) a third mode, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
292
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(341 citation statements)
references
References 30 publications
39
292
6
Order By: Relevance
“…[48] The multimodal nature of the lower end of the sea spray aerosol size distribution has also been noted in recent group bubble experiments [Fuentes et al, 2010b;Sellegri et al, 2006]. The multiple modes provide further evidence that there may, in fact, be a number of different production Increasing bubble persistence Figure 6.…”
Section: Implications For Particle Production Mechanismsmentioning
confidence: 87%
See 2 more Smart Citations
“…[48] The multimodal nature of the lower end of the sea spray aerosol size distribution has also been noted in recent group bubble experiments [Fuentes et al, 2010b;Sellegri et al, 2006]. The multiple modes provide further evidence that there may, in fact, be a number of different production Increasing bubble persistence Figure 6.…”
Section: Implications For Particle Production Mechanismsmentioning
confidence: 87%
“…[5] However, the theory fails to account for the even smaller sea spray particles observed in many recent laboratory and ambient studies [Clarke et al, 2006;Fuentes et al, 2010a;Hultin et al, 2010;Keene et al, 2007;Martensson et al, 2003;Modini et al, 2010;Russell and Singh, 2006;Sellegri et al, 2006;Tyree et al, 2007]. Specifically, there is little explanation for the dominant SSA accumulation mode centered at~0.1-0.2 mm dry particle diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,6,14 Detailed studies of SSA production methods have shown that both breaking waves and plunging waterfall techniques replicate ambient SSA subpopulations of particles with the proper size and physical and chemical properties. 2,5 Other variables, such as temperature, 15 surfactant chemistry, 13,16 and white cap foam formation 5 are also critical factors in producing real world SSA populations. The development of these innovative laboratory-based methods has opened the doors for exploring the composition, reactivity, and properties of a globally abundant tropospheric aerosol, fresh SSA, under controlled conditions.…”
Section: ■ Producing Representative Ssamentioning
confidence: 99%
“…Several different methods have been used to generate surrogate marine aerosols within enclosed tanks including pressurized atomizers (Svenningsson et al, 2006;Riziq et al, 2007;Saul et al, 2006;McNeill et al, 2006;Braban et al, 2007;Niedermeier et al, 2008;Taketani et al, 2009), forcing air through glass filters or sintered materials (Cloke et al, 1991;Martensson et al, 2003;Sellegri et al, 2006;Keene et al, 2007;Tyree et al, 2007;Wise et al, 2009;Hultin et al, 2010;Fuentes et al, 2010) and by a plunging water jet (Cipriano and Blanchard, 1981;Sellegri et al, 2006;Facchini et al, 2008;Fuentes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%